A case of melanism in a Gentoo Penguin (Pygoscelis papua) at Esperanza/Hope Bay, Antarctica - Nigro, Rocio; Silvestro, Anahí Mariel; Juares, Mariana Alejandra; Di Marco, Pamela (Polar Biology)
Gentoo Penguin (Pygoscelis papua) is a species that reproduces in Antarctica and sub-Antarctic islands. During 2022 a Gentoo Penguin with an unusual plumage coloration was recorded at Esperanza/Hope Bay, north of the Antarctic Peninsula (63°24′ S, 57°01′ W). The coloring of plumage is achieved by two types of pigments known as carotenoids and melanins. Two different types of melanin (phaeomelanin and eumelanin) are responsible of producing different pigmentation patterns that oscillates between reddish-blackish coloration. The unusual coloration of the penguin was identified as melanism, a genetic condition that causes an excess of melanin pigment in feathers. This particular individual appeared to be in good health and exhibited normal behavior. As far as we know this is the second official report of melanism for the species since the first one in 1997 and it is the first report for the colony. Fil: Nigro, Rocio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Silvestro, Anahí Mariel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Centro de Investigación Esquel de Montaña y Estepa Patagóica. Universidad Nacional de la Patagonia "San Juan Bosco". Facultad de Ciencias Naturales - Sede Esquel. Centro de Investigación Esquel de Montaña y Estepa Patagónica; Argentina Fil: Juares, Mariana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Di Marco, Pamela. Comando Conjunto Antártico Argentino; Argentina